Improvement of heat-sealing strength of chitosan-based composite films and product costs analysis in the production process - Jongjun, Yuthanarong; Pornprasert, Peema; Prateepchanachai, Sarinya (Journal of Applied Research on Science and Technology (JARST), 2024)
The primary objective of this study was to enhance the heat-sealing strength of composite films made from chitosan and analyze the associated product costs. The approach adopted involved formulating chitosan-based composite films by incorporating gelatin and green seaweed extract. This strategic combination resulted in a notable improvement in heat-sealing strength. The ensuing attributes underwent meticulous examination, encompassing seal strength, FTIR spectroscopy, FE-SEM surface morphology analysis, and DSC thermal properties determination. Data analysis was rigorously conducted using the SPSS program, with outcomes presented as mean values accompanied by standard deviations. Disparities were discerned at a 95% confidence level, ensuring statistical robustness. The findings unveiled that the incorporation of 10% gelatin and 1% green seaweed extract substantially enhanced the seal strength of the chitosan-based composite films. Notably, the introduction of green seaweed extracts disrupted interactions between chitosan’s structure and various molecular vibrations. This disruption, coupled with increased ionic interactions and hydrogen bonding, led to improved molecular interdiffusion, ultimately resulting in modified heat sealability. The study identified the optimized conditions as 10% gelatin and 1% green seaweed extract concentrations, which produced the highest seal strength at 19.4 N/m. Further evidence from scanning electron microscopy demonstrated improved interfacial adhesion, attributed to the adjusted surface morphology. The film surface did not contain small scattered particles and presented a smooth phase. This suggests that the chitosan-based composite achieved good interfacial adhesion between the two components in these films. As an essential aspect for practical application, the total production cost of the films was determined to be 606.84 baht. This information renders the data collection from the study valuable for companies seeking to enhance production efficiency and overall profitability.